Organizational culture as a root of performance improvement: research and recommendations - Che Rose, Raduan; Samy, Naresh Kumar; Abdullah, Haslinda; Goh, Yeng Ling (Academy of Taiwan Information Systems Research, 2008)
Bearing in mind the rapidly growing foreign subsidiaries, the appropriate organizational culture for the efficient deployment of resources and consequently for an encouraging outcome on the business performance would appear to be an imperative consideration for business expansions. Internationalization of business may perhaps force not merely the restructuring of cultural values but to consider the overture of different cultural practices which perhaps leads to a superior organizational performance. One could note that the organizational culture literature reinforce that culture is imperatives for organizational change efforts, deployment of human resources and on the whole sustaining competitive edge. Thus leaders are challenged to determine the most valuable culture for their organization and revolutionize the organizational culture as to address the business world mutiny. This paper attempts to provide some insights into the organizational culture and how it might assist in increasing organizational performance. Future research direction been highlighted.